Quotidienneté et résistance - Jad HATEM (Studia Universitatis Babeș-Bolyai. Philosophia)
Daily Life and Resistance. Between daring project and tranquility, everyday life chooses the second term, the first threatening the habituality of serene existence. To do this, it deploys a minimal morality and, above all, a structure of resistance. The study is based on Andrei Pleşu, Simone de Beauvoir, and Josep Maria Esquirol.